Hybrid treatment of a true thyreocervical trunk aneurysm in a patient with Type B aortic dissection - Baikoussis, Nikolaos G. (Ann Card Anaesth, 2016)
We would like to describe a case with a complex aortic disease treated in hybrid fashion. We present an interesting case of a 65-year-old man with a medical history of hypertension, hyperlipidemia, and coronary artery disease percutaneously treated. An acute Type B aortic dissection occurred and treated with the implantation of a stent-graft which occluded the left subclavian artery due to its extension to the aortic arch. This event required a carotid-subclavian artery bypass due to ischemia of the left arm. An aneurysm in the innominate artery also detected, was treated with another stent-graft implantation 3 months later. At 5-year follow-up, an aneurysm of the thyreocervical trunk was found while the stent-graft of the aorta was well-tolerated without endoleak and the carotid-subclavian graft was patent. The aneurysm was asymptomatic but considering the risk of spontaneous rupture of an aneurysm of this size, elective surgery was indicated. Because the aneurysm was very close to the brachiocephalic bifurcation, open surgical repair would require a sternotomy. The right common carotid artery and right subclavian artery were exposed. The thyrocervical trunk, right internal mammary artery and right vertebral artery were occluded by ligations to isolate the aneurysm. An 8-mm Dacron graft was anastomosed end-to-end to the distal part of subclavian artery. We would like through this case, discuss the role of the hybrid cardiovascular surgery to minimize the postoperative complications in complex cardiovascular pathology. We also discuss the international bibliography about the thyreocervical trunk aneurysm and the treatment options.